Balancing Act: Intellectual Property Rights Enforcement and Its Impact on Creativity in the South Korean Pop Music Industry - Seo-Jun Cho (Studies in Social Science & Humanities, 2024)
This paper explores the relationship between intellectual property rights enforcement and creativity in the South Korean pop music industry. Through qualitative interviews with industry professionals and an analysis of South Korea’s copyright laws, this study reveals how stringent copyright enforcement influences music production and innovation. The findings suggest that while copyright laws are essential for protecting creators’ rights, they also pose challenges for creative freedom. This paper contributes to the discourse on copyright law and creative industries, highlighting the need for policies that both protect intellectual property and encourage artistic innovation.